2011
DOI: 10.1007/s10554-011-9902-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coronary calcification on the diagnostic accuracy of 64-slice computed tomography coronary angiography: a systematic review and meta-analysis

Abstract: To determine via meta-analysis the diagnostic accuracy of 64-slice computed tomography coronary angiography (CTA) for assessment of significant obstructive coronary artery stenosis at different coronary artery calcium score (CACS) levels. Data of 12,053 versus 5,890 segments, 906 versus 758 arteries and 1,120 versus 514 patients in low versus high CACS subgroups from 19 eligible studies were compared. The per-patient prevalence of coronary artery disease was 48% versus 68%, respectively. Subgroups were stratif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 40 publications
2
48
0
Order By: Relevance
“…The presence of calcium in the coronary arteries (in particular, CACS ≥ 400 or CACS ≥ 600) significantly reduces the specificity of CCTA. (36) On the basis of this finding and the results obtained from our study, in which patients with double-and triple-vessel disease obtained a higher CACS, we confirmed that CCTA has a negative predictive value, as widely described in the scientific literature. (37) It has been widely demonstrated that the sensitivity of CCTA in identifying severe stenosis is very high; on the contrary, the specificity tends to be lower due to the tendency of CCTA to overestimate stenosis, especially in calcified plaques.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The presence of calcium in the coronary arteries (in particular, CACS ≥ 400 or CACS ≥ 600) significantly reduces the specificity of CCTA. (36) On the basis of this finding and the results obtained from our study, in which patients with double-and triple-vessel disease obtained a higher CACS, we confirmed that CCTA has a negative predictive value, as widely described in the scientific literature. (37) It has been widely demonstrated that the sensitivity of CCTA in identifying severe stenosis is very high; on the contrary, the specificity tends to be lower due to the tendency of CCTA to overestimate stenosis, especially in calcified plaques.…”
Section: Discussionsupporting
confidence: 89%
“…Second, the absence of a high value of CACS does not completely rule out the possibility of CAD and, conversely, CACS cannot assess those plaques that are non-calcified or partially calcified. (36) For this reason, a major limitation regarding the diagnostic accuracy of CCTA is coronary calcifications. The presence of calcium in the coronary arteries (in particular, CACS ≥ 400 or CACS ≥ 600) significantly reduces the specificity of CCTA.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Even with 64-slice and newer CT systems, the sensitivity and specificity of coronary CTA for significant stenosis remains high in the presence of severe calcifications. 28 Because motion further intensifies calcium-related artefacts, 26 patients should be screened for compliance to breath-hold and HR stability.…”
Section: Patient Selection and Preparationmentioning
confidence: 99%
“…Bulky calcifications can be expected in 10 % of coronary segments in patients with intermediate pre-test likelihood of coronary artery disease, and of these one in four are associated with significant stenoses [19]. Bulky calcifications typically lead to overestimation of lesion severity (false positive diagnosis) [19][20][21][22] related to limited spatial resolution of CCTA and the resulting visual impression known as the 'blooming effect'. Whether focal segmental calcifications can help predict the probability of underlying coronary stenosis was the research question addressed by this study.…”
Section: Discussionmentioning
confidence: 99%